EFFECTE OF PHOSPHATE FERTILIZER ON GROWTH AND YIELD OF FIVE CULTIVARS BREAD WHEAT - & et al., Kadum (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was carried out at the College of Agriculture, Duhok University to study the effect of phosphorous levels (25, 30, and 35) kg P ha-1 in addition to control treatment and five wheat varieties (SDRAA-1, Sham-4, Maxipak, Abugraib-3, and JAWA-13) on yield and yield components of cultivated studied wheat varieties in calcareous soil during winter season (2014- 2015). The experiment units were laid out in the factorial arrangement using randomized complete block design (RCBD) with three replicates. The results revealed that wheat varieties were significantly affected on plant height, protein percent, leaf area, date of flowering, grain weight spik-1, No. of grain spike-1, 1000- grain weight, chlorophyll, harvest index, and grain yield. While the phosphorous levels exhibited significant effects on grain weight spike-1, number of grain spike-1, harvest index, and grain yield. While the interaction between phosphorous and varieties, show significant effects. The variety JAWA-13 was superior in traits of protein content, phosphorous concentration, harvest index, grain weight.